Safety and Efficacy of Asciminib in Chronic Myeloid Leukemia Patient with Chronic Kidney Diseases: A Case Report - Awni Alshurafa; Afshan Adil; Mohamed A. Yassin (Case Reports in Oncology, 2024)
Introduction: Chronic myeloid leukemia (CML) is characterized by the presence of the BCR::ABL1 fusion gene, and the advent of tyrosine kinase inhibitors (TKIs) has revolutionized its therapeutic landscape. Asciminib, a STAMP inhibitor, emerges as a promising option for patients unresponsive or intolerant to multiple conventional TKIs. However, the safety and efficacy of asciminib in individuals with chronic kidney disease remain understudied. Case Presentation: In this report, we detail the case of a 62-year-old patient with CML and stage 3 chronic kidney disease, who faced intolerance to traditional TKIs primarily due to fluid retention. The transition to asciminib therapy resulted in a profound molecular response and did not exacerbate renal function, effectively addressing the fluid retention issue. Conclusion: This case highlights the potential of asciminib as a viable therapeutic alternative for CML patients with chronic kidney disease, particularly those intolerant to standard TKIs. Further research is warranted to establish the broader safety and efficacy profile of asciminib in this patient population.